The Criminalization of Public Policy and the Governance Dilemma: Reconstructing the Legal Boundaries between Administrative Discretion and Abuse of Authority - Haniyah; Muhammad Irfan Hibatulloh Alquds (Universitas Darul Ulum, 2026)
The expanding use of criminal law in administrative governance has increasingly reshaped the relationship between public accountability and policy-making in Indonesia. Public officials frequently face criminal investigation for discretionary decisions made within their official authority, particularly when policy failures, procedural irregularities, or state financial losses arise after policy implementation. Consequently, the boundary between legitimate administrative discretion and criminal abuse of authority has become increasingly unclear, creating legal uncertainty and affecting governance effectiveness. This study examines how the criminalization of public policy influences administrative discretion and bureaucratic governance in Indonesia. Using a socio-legal and conceptual legal research approach, the study analyzes legislation, legal doctrines, judicial reasoning, governance theory, and scholarly literature concerning corruption, public administration, and state accountability. The findings reveal that outcome-oriented criminal liability increasingly shifts accountability from intent toward policy consequences. As a result, policy failure and procedural irregularity are frequently treated as indicators of criminal wrongdoing despite the absence of corrupt intent or personal benefit. Excessive criminalization also contributes to defensive bureaucratic behavior characterized by excessive procedural caution, declining policy innovation, delayed decision-making, and weakened administrative responsiveness. This study argues that accountability mechanisms must operate within proportionate legal boundaries. Accordingly, the article proposes a differentiated accountability framework in which criminal sanctions remain focused on intentional abuse of authority, while good-faith administrative errors and policy failures are addressed primarily through administrative supervision and governance correction mechanisms.